Pengaruh Umur Kematian Tanaman Sumber Inokulum Banana Bunchy Top Virus Terhadap Efisiensi Penularannya (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2022)
BBTV is one of the important diseases in banana plants, the transmission of BBTV can be carried out by Pentalonia nigronervosa. In some banana plantations infected plants are usually cut down because they are considered unable to produce optimal production. The felled plants will then be placed around healthy plantations, this situation is thought to have the potential as a place for P. nigronervosa to temporarily live and spread the virus to other healthy plants. This study aims to determine the ability of dead plants that host P. nigronervosa to re-transmit the virus to healthy plants. The study was conducted using a Randomized Block Design (RAK) with six treatments on the day of death of infected plants, namely, 0, 5, 10, 15, 20, and 25 days, with five replications. From the results of the study, it was found that plants infected by BBTV still had potential to transmit the virus to healthy plants through the P. nigronervosa. Transmission of BBTV from dead plants on the fifth day resulted in the highest average of BBTV infection. The incubation period of virus in plants ranged from 30-53 days after inoculation. From this research, it is hoped that farmers will pay more attention to thoroughly eradicate banana plants infected by BBTV, removed all plant and suckers thoroughly together with their corms.